Styles of business communication and environment of the organization: factors of mutual determination - Tolochek, Vladimir A.; Vilches-Nogerol, Veronika V.; Sizova, Larisa A. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The purpose of the research: the study of relations of the effectiveness of activities and social success of subjects in the social environment of modern organizations. Hypotheses: 1) the business communication styles of the subjects are influenced by the conditions of the social environment (micro- and meso-media organizations); 2) business communication styles of subjects are associated with the stages of the evolution of the organization. The subject of the research is the business communication styles of subjects (successful professionals-managers and heads of departments of a large commercial company (85 people); nurses and senior nurses (142 people). Methods: expert survey; psychodiagnostics; research methodology «Business communication styles» by V. A. Tolochek, observation included. The formation and consolidation of typical business communication styles of modern organizations is associated with their working conditions (official duties, relationships in working groups, with the management of departments, declared and latent features of the organization’s corporate culture, traditions, etc.). The styles of business communication of subjects are associated with the stages of the evolution of the organization. The conditions of the social environment (micro- and meso-environment of the organization) influence the formation and consolidation of individual styles of individual subjects; a set of styles of staff influences the dynamics of an organization’s evolution. More constructive styles of nurses are combined with such «life cycles of the organization» as «maturity» («stability»); less constructive styles of managers – with the stages of «recession» and «death». The styles of representatives of socionomic professions (managers and heads of divisions of a large commercial company) are characterized by high and moderate severity of style components, reflecting the features of the subjects’ communications and supporting its success. When factor analysis identifies six well-interpreted factors that characterize the relevant styles of business communication employees. Substantially, in accordance with the composition of the variables and their factor weights, the selected factors as styles received the name: first factor – formalization of interactions, minimization of cooperation, promotion of partner’s activity; second – softness and evasiveness, distancing from a partner; third – hardness and distancing, persistence, power opposition; fourth – high activity and inconsistency, inflexibility, non-vision of interaction prospects; fifth – liberal style; sixth – stiffness, distancing, orientation to compromise solutions. Taking into account the requirements to the activities of managers of an advertising and consulting company, all six allocated styles should be considered ineffective. Styles of representatives of the second socionomic professions (nurses and senior nurses) are characterized by high and moderate severity of style components, reflecting the features of communications and supporting its success. In factor analysis, six well-interpretable factors are distinguished: the first factor, according to the composition and weight of its forming variables, was named rationality, constructiveness, hardness, compliance with regulations, partner support; second – democracy, flexibility, emotionality, close psychological distance; third – authoritarianism, rigidity, hardness, brevity of orders and interactions; fourth – conflict, inconsistency of behavior; fifth – distance, propensity to formalize communications; sixth – compromise strategy. Taking into account the requirements of the activities of nurses, first, second and third styles can be considered effective, one (sixth) – conditionally effective, fourth and fifth styles – ineffective psychological systems.